Pemberdayaan Masyarakat Desa Widodaren dengan Menciptakan Kebun Gizi sebagai Upaya Pencegahan Stunting : Pemberdayaan Masyarakat Desa Widodaren dengan Menciptakan Kebun Gizi sebagai Upaya Pencegahan Stunting - Pibriyanti, Kartika; Mufidah, Indahtul; Fajr Rooiqoh, Qothrunnadaa; Akhiriana, Enik; Luthfiya, Lulu’; Amala, Nur (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
The stunting rate is increasing every year in Indonesia. The impact caused by stunting in the medium term is in the form of low intelligence and cognitive abilities, and risk. The long term is the quality of human resources and the problem of degenerative diseases in adulthood. Prevention of stunting can be done one of them by implementing specific nutrition programs with food security indicators through the development of local food based on nutrition gardens. This research method uses descriptive qualitative method. The activity begins by looking at the knowledge of Family Welfare Development (PKK) and Integrated Sevices Post (Posyandu) cadres related to the basic skills of Health Integrated Sevices Post cadres. Statistical test results showed a significant difference of 0.000 between the mean before and after the material exposure of 25 basic skills of Posyandu cadres in PKK and Posyandu cadres in Widodaren Village. This activity involved PKK women and Posyandu cadres with the implementation of a nutrition garden using aquaponic technology, a technology that combines fish and vegetable cultivation in one cultivation period. The next activity is processing the results of the nutrition garden in the form of vegetables and catfish into nutrient-dense foods such as processed nuggets and dim sum. Local food-based nutritional gardens can be an effort to prevent stunting.